Analysis of the effects of conservatism in accounting information after the 2011 change in the basic conceptual pronouncement - Kronbauer, Clóvis Antônio; Marquezan, Luiz Henrique Figueira; Barbosa, Marco Aurélio Gomes; Diehl, Carlos Alberto (Review of Business Management, 2017)
Purpose – This study researches whether the change in NBC TG, promoted in 2011, that excluded Prudence (Conservatism), had any effect on companies’ accounting information. Design/methodology/approach – Quantitative approach, using a linear regression based on the Basu (1997) method, Wilcoxon tests and t test, on a sample with 109 companies, listed on the BM&FBovespa, from 2008 to 2013. Findings – The results indicate that conservatism is present in accounting for the entire period, and changes do not occur in this feature of the accounting information as of 2011. Originality/value – This research reinforces the perception of the superiority of economic interest, in particular for possible tax gains, to the detriment of accounting information quality, be it of regulatory origin or another.